Consideration of the Somatotype in the Development of Primary Teaching Swimming Methods of Children - Olga Obrazhey (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2018)
The study reveals the issue of studying the physical development and a somatotype of a child to develop a methodology for initial swimming training in open water bodies. The following methods are used in the work: analysis and generalization of literary sources, medical-biological methods (anthropometric), pedagogical observation, methods of mathematical statistics with using «Excel 2000». The buoyancy of primary school children was diagnosed in real conditions of swimming training lessons with two tests: horizontal and vertical. The survey sample consisted of children aged 8–9, out of which there were 15 girls and 14 boys. They were at «Swimming school» in Kherson during June 2016. All children were able to swim. An individual assessment of the degree of anthropometric development indicators using centimetric tables revealed that children with an average level of physical development predominated in two sexually active age groups, but there was a significant percentage of children with a low level of physical development. In the course of the study, it was discovered that boys and girls of hypersthenic somatotype had high level in two exercises; children of primary school age of normostenic and asthenic somatotype had less buoyancy. The analyzed values of the correlation coefficients indicated that there was an insignificant connection between height and buoyancy.  The study observed the relationship between the indicators of body weight and the result of buoyancy test. The most significant relationship wass between the result of the chest volume and the result of the buoyancy tests.